Electrical modulation properties of DNA drug molecules. Issue 3 (30th June 2022) - He, Lijun; Xie, Zhiyang; Long, Xing; Zhang, Chaopeng; Qi, Fei; Zhang, Nan
Abstract: DNA drug molecules are not only widely used in gene therapy, but also play an important role in controlling the electrical properties of molecular electronics. Covalent binding, groove binding and intercalation are all important forms of drug–DNA interaction. But its applications are limited due to a lack of understanding of the electron transport mechanisms after different drug–DNA interaction modes. Here, we used a combination of density functional theory calculations and nonequilibrium Green's function formulation with decoherence to study the effect of drug molecules on the charge transport property of DNA under three different binding modes. Conductance of DNA is found to decrease from 2.35E-5 G0 to 1.95E-6 G0 upon doxorubicin intercalation due to modifications of the density of states in the near-highest occupied molecular orbital region, δG = 1105.13%. Additionally, the conductance of DNA after cis -[Pt(NH3)2(py)Cl]+ covalent binding increases from 1.02E-6 G0 to 5.25E-5 G0, δG = 5047.06%. However, in the case of pentamidine groove binding, because there is no direct change in DNA molecular structure during drug binding, the conductance changes before and after drug binding is much smaller than in the two above cases, δG = 90.43%. Our theoretical calculations suggest that the conductance of DNA can be regulated by different drug molecules or switching the interaction modes between small molecules and DNA. This regulation opens new possibilities for their potential applications in controllable modulation of the electron transport property of DNA.